Pengaruh Endorsement Influencer Terhadap Perilaku Konsumtif dan Minat Menabung Siswa SMKN 1 Palembang - Ramadani, Rahmi; FH, Yuliana (Universitas Hamzanwadi, 2025)
The development of technology in the current era is so rapid, one of the phenomena that is developing is influencers for product endorsements. In the digital era, influencer endorsements have an important role in influencing students' purchasing decisions and financial behavior. This study aims to determine the influence of influencer endorsements on consumptive behavior and savings interest of class X students majoring in Financial and Institutional Accounting at SMK Negeri 1 Palembang. This study uses a quantitative survey method. The sample consisted of 59 students of SMK Negeri 1 Palembang with the probability sampling method with a simple random sampling technique. The data collection technique uses questionnaires. The linear regression test showed a value of ,t-count .≥ ,t-table .or 11.3431 ≥ 1.671, meaning that the hypothesis accepted in this study had a significant effect of influencer endorsement on the consumptive behavior of class x students majoring in financial accounting and institutions at SMK Negeri 1 Palembang, and also obtained the results of the t-test, namely ,t-count. ≥ ,t-table . or 20.11 ≥ 1.671, meaning that the hypothesis accepted in this study has a significant effect of influencer endorsement on the saving interest of class X students majoring in financial accounting and institutions at SMK Negeri 1 Palembang